2021
DOI: 10.1017/s0022050720000613
|View full text |Cite
|
Sign up to set email alerts
|

Temperature, Disease, and Death in London: Analyzing Weekly Data for the Century from 1866 to 1965

Abstract: Using novel weekly mortality data for London spanning 1866-1965, we analyze the changing relationship between temperature and mortality as the city developed. Our main results show that warm weeks led to elevated mortality in the late nineteenth century, mainly due to infant deaths from digestive diseases. However, this pattern largely disappeared after WWI as infant digestive diseases became less prevalent. The resulting change in the temperature-mortality relationship meant that thousands of heat-related dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Woods and Shelton (1997, p. 48, Figure 12), Woods (2000, p. 275, Figure 7.12) and Galley (2021, p. 123, Figure 4) have very effectively illustrated the fact that England and Wales' infant mortality rate (IMR) remained relatively stable over the second half of the 19th century, before rising across the 1890s and then turning sharply downwards at the start of the 20th century. Woods and his associates (Woods, 2000;Woods et al, 1988Woods et al, , 1989) demonstrated that the increase in the IMR during the 1890s was due to an upsurge in diarrhoeal deaths as the inadequate sanitation systems and poor hygiene in urban areas were severely strained by a series of long hot, dry summers in the later part of the decade (see Hanlon et al, 2021). More recently, Galley (2021) has suggested that more analysis of the relationship between infant mortality and the weather is needed before any firm conclusions can be reached on the nature of the interaction between them.…”
mentioning
confidence: 99%
“…Woods and Shelton (1997, p. 48, Figure 12), Woods (2000, p. 275, Figure 7.12) and Galley (2021, p. 123, Figure 4) have very effectively illustrated the fact that England and Wales' infant mortality rate (IMR) remained relatively stable over the second half of the 19th century, before rising across the 1890s and then turning sharply downwards at the start of the 20th century. Woods and his associates (Woods, 2000;Woods et al, 1988Woods et al, , 1989) demonstrated that the increase in the IMR during the 1890s was due to an upsurge in diarrhoeal deaths as the inadequate sanitation systems and poor hygiene in urban areas were severely strained by a series of long hot, dry summers in the later part of the decade (see Hanlon et al, 2021). More recently, Galley (2021) has suggested that more analysis of the relationship between infant mortality and the weather is needed before any firm conclusions can be reached on the nature of the interaction between them.…”
mentioning
confidence: 99%
“…It is estimated that a one‐percentage‐point increase in the population with access to a constant water supply caused as much as a 0.4 per cent reduction in mortality from waterborne disease. Among other articles on the topic of London was one by Hanlon et al., who analyse the effect of temperature on mortality in the capital city over the century from 1866 to 1965. Using weekly temperature data and weekly mortality data disaggregated by cause and age group, they arrive at a number of conclusions.…”
mentioning
confidence: 99%